Envisioning urban villages : a critique of a movement and two urban transformations - Thompson-Fawcett, M (1998)
Shifts in developmental and environmental imperatives in the late 1980s and early 1990s have prompted concomitant reassessments of urban management practice. In this context, the urban village discourse has emerged as an alternative take on how to create the built landscape. The ideas promoted in the discourse have been quickly adopted into national policy and implemented in urban development projects. However, it is the argument of this thesis that such endorsement of urban village principles has been hasty and uncritical. Employing the urban village as a material example, this thesis examines the implications of the production of urban form in the communication of meanings and social relations. The approach uses 'landscape' as an organising concept. This approach acknowledges the ideological foundations of urban transformation processes and the role that the built landscape has in signifying societal intentions. What the investigation confirmed was that not only does the urban village discourse have a concern with fashioning physical environments, but it also attempts to procure specific social outcomes through the built form. Case studies of two urban village landscapes, that are currently under construction, are used to progress this argument. The first is a green field extension to a small county town, the Poundbury project in Dorchester, Dorset. The second is a regeneration scheme in the centre of a major city, the Crown Street project in Glasgow. Through these two urban landscapes it is possible to analyse the divergent application of urban village premises and ideologies amidst competing influences. The projects illustrate the diversity in physical form and economic context that is possible within the urban village discourse. However, their social agendas are closely aligned. Three principal arguments are made in the thesis. Firstly, that urban village conception and construction of the built environment communicates a specific conservative social order. Secondly, that when embracing new paradigms the planning and development communities need to make themselves aware of the intrinsic implications and complex ideological enterprises associated with them. Finally, that a critical landscape approach is a powerful tool for unveiling the foundations of newly emerging planning visions.